Reorienting Public Agriculture R&D to Achieve Resilient and Sustainable Food and Agriculture System in Indonesia - Sudaryanto, Tahlim; Suryana, Achmad; Purba, Helena Juliani; Rafani, Iqbal; Maghraby, Wahida; Yofa, Rangga Ditya; Savitri, Sheila; Zhou, Yuan; Kretschmer, Alva (STI Policy and Management Journal, 2024)
Indonesia's agriculture is evolving towards modern, high-value, and market-driven practices, aligning with Sustainable Development Goals (SDGs). Technological change, markets, institutions, climate change, and government policies influence the performance of agriculture. The government plays a major role in agricultural innovation through investment in agricultural Research and Development (R&D), focusing on food and nutrition security, climate resilience and sustainability, and agricultural transformation. This paper aims to analyze the level and structure of agricultural R&D funding in Indonesia and draw recommendations for reorienting future agriculture R&D priorities. The analysis is based on a series of focused group discussions and secondary data from related stakeholders, enriched by information from the literature review. This study assesses Indonesia's agricultural R&D funding, finding it minimal at less than 0.2% of agricultural GDP, mostly public-funded. Farmers are slow to adopt these innovations despite substantial spending on technology dissemination. Gaps exist in accelerating agricultural transformation and technology adoption. Based on the findings, we propose seven recommendations for reorienting the R&D funding, including increasing the funding level of public research and better disseminating research results Keywords: agricultural R&D, gaps, recommendation, reorienting, Indonesia